Language funeral rituals in the comments of Internet users - Trysińska, Magdalena (Papers in Linguistics, 2021)
The article analyses comments of users placed under articles published on the Internet informing about the death of public figures: a famous film producer, a popular actor of the older generation and a politician associated with the ruling party. It is assumed that on this basis it is possible to observe and predict changes in the customs of a given social group, especially in the case of a communication situation related to a social taboo. The research used pragma-linguistic methodology. Selected speech acts are units of description: a prayer for the deceased, condolences, and expressions of grief. These are prototypical communication behaviours that constitute the funeral ritual. However, these speech acts did not always communicate the goals inscribed in their modal framework. There were condolences that did not express regret, prayers accompanied by criticism of the deceased or open statements of lack of regret about the death of the dead man. The analysis showed that the percentage of individual acts of speech in the comments of Internet users depends on whose death is commented on. Decisive factors here comprise: the age of the dead, the fact whether they often appeared in the media and in what circumstances, whether they were involved in scandals and the circumstances of their death, finally, personal sympathies and antipathies of Internet users not only towards the dead, but also their families.